Audio mastering the artists : discussions from pre-production to mastering - Hepworth-Sawyer, Russ; Hodgson, Jay (Perspectives on music production series, 2019)
"Audio Mastering: The Artists collects more than twenty interviews, drawn from more than 60 hours of discussions, with many of the world's leading mastering engineers. In these exclusive and often intimate interviews, engineers consider the audio mastering process as they, themselves, experience and shape it as the leading artists in their field. Each interview covers how engineers got started in the recording industry, what prompted them to pursue mastering, how they learned about the process, which tools and techniques they routinely use when they work, and a host of other particulars of their crafts. We also spoke with mix engineers, and craftsmen responsible for some of the more iconic mastering tools now on the market, to gain a broader perspective on their work."--Publisher's description